Security mechanisms for mobile agent-based E-commerce system - Yao, Gong Xuan (2008)
In this thesis, security requirements for agent protection and host protection are discussed and approaches on how to guarantee them are presented. We propose a security framework in which all necessary security services and the solutions are provided. Then a secure payment protocol based on Shamir’s secret sharing scheme is developed for agent protection, in which more than one agent are used in order to build a secure mobile agent environment.